2017
DOI: 10.1111/jbi.13064
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene refugia in the Chihuahuan Desert: the phylogeographic and demographic history of the gymnosperm Ephedra compacta

Abstract: Aim We investigate the influence of late Neogene orogenic activity and Pleistocene glacial‐interglacial cycles on intraspecific divergence and demographic history in the gymnosperm shrub Ephedra compacta. We test refugia hypotheses to explain geographical patterns of genetic diversity and phylogeographic structure in a warm North American desert that reaches inter‐tropical latitudes. Location Chihuahuan Desert, Mexican Plateau, Sierra Madre Oriental, Tehuacán Valley. Methods Geographical patterns of genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 80 publications
3
25
0
2
Order By: Relevance
“…According to vegetation records, pinyon‐juniper‐oak forest was the predominant vegetation of the Chihuahuan Desert at that time (van Devender, ; van Devender & Spaulding, ; Rebernig et al, ). This expansion around the time of the Last Glacial Maximum has been detected in other ENM studies on a number of plant groups in the Chihuahuan Desert (Angulo, Amarilla, Anton, & Sosa, ; Loera et al, ; Ruiz‐Sanchez et al, ; Scheinvar et al, ). Moreover, during the Pleistocene, cooler wetter climates were mostly present the Chihuahuan Desert, and mesic woodland essentially dominated the landscape (Holmgren, Penalba, Rylander, & Betancourt, ; MacKay & Elias, ).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…According to vegetation records, pinyon‐juniper‐oak forest was the predominant vegetation of the Chihuahuan Desert at that time (van Devender, ; van Devender & Spaulding, ; Rebernig et al, ). This expansion around the time of the Last Glacial Maximum has been detected in other ENM studies on a number of plant groups in the Chihuahuan Desert (Angulo, Amarilla, Anton, & Sosa, ; Loera et al, ; Ruiz‐Sanchez et al, ; Scheinvar et al, ). Moreover, during the Pleistocene, cooler wetter climates were mostly present the Chihuahuan Desert, and mesic woodland essentially dominated the landscape (Holmgren, Penalba, Rylander, & Betancourt, ; MacKay & Elias, ).…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, instead of considering the Mexican Plateau as a centre of origin of the flora of the Chihuahuan Desert, phylogeographic research has hypothesized that the southern region of the Mexican Plateau acted as refugium for different plant lineages that migrated either from North or South America (Loera, Ickert‐Bond, & Sosa, ; Ruiz‐Sanchez, Rodriguez‐Gomez, & Sosa, ; Scheinvar, Gámez, Castellanos‐Morales, Aguirre‐Planter, & Eguiarte, ; Vásquez‐Cruz & Sosa, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, results of current ENM and palaeomodeling show that the area currently occupied by studied species is substantially larger than it was during the LIG period and the LGM, suggesting that it has been gradually expanding northward since the LIG period. Previous phylogeographic studies that included plant populations of the Valles Centrales and the Tehuaca´n-Cuicatla´n Valley have shown that their ranges contracted during interglacials and then expanded to colonize northern xeric regions during the glacial periods (the Meztitla´n Valley and the Chihuahuan Desert; e.g., Loera, Ickert-Bond, & Sosa, 2017;Ruiz-Sanchez et al, 2012;Scheinvar et al, 2017) or expanded during the warm/humid LIG period and contracted to one or more southerly refugia during cold/dry glacial maxima (Cornejo-Romero et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that arid environments have experienced drastic climate changes during the last glacial period (Metcalfe, 2006), especially during the Last Inter Glacial (LIG; 1.2×10 5 -1.4×10 5 years ago) and the Last Glacial Maximum (LGM; about 2.2×10 4 years ago) periods. Some studies show that several native species from arid environments have had changes in their distribution range in response to past climatic fluctuations, as is the case of Berberis trifoliolata (Berberidaceae; Angulo et al, 2017), Ephedra compacta (Ephedraceae; Loera et al, 2017), Larrea tridentata (Zygophyllaceae; Hunter et al, 2001) and Lindleya mespiloides (Rosaceae; Vásquez-Cruz and Sosa, 2016). Because T. frutescens is mainly distributed in arid environments, it is likely that those climatic oscillations affected its distribution range.…”
Section: Introductionmentioning
confidence: 99%